N-(Methyl-D3)-acetamide - F Fillaux, CNRS, Thiais, France (My University, 1993)
Inelastic Neutron Scattering spectrum of N-(Methyl-D3)-acetamide, C₃H₄NOD₃, measured on the TFXA instrument. CH3-CO-NH-CD3.
Keywords: TFXA